SYNTHESIS AND BIOLOGICAL EVALUATION OF SOME CHLOROSUBSTITUTED-1, 3-THIAZOLES - A V GAJBHIYE; P R RAJPUT (International Journal of Pharma and Bio Sciences, 2013)
A Simple and convenient protocol is described for preparation of some new 5-(2’-hydroxy-3’,5’-dichlorophenyl)-4-(4’-chlorobenzyl)-2-amino-1,3-thiazole and 5-(2’-hydroxy-3’,5’-dichlorophenyl)-4-(4’-chlorobenzyl)-2-aminophenyl-1,3-thiazole, were synthesized by refluxing dibrominated chalcone with thiourea or N-phenyl thiourea in good yields. The newly synthesized titled compounds were screened for their antibacterial activities against pathogens such as staphylococcus aureus, p.aeruginosa, salmonella typhi. Some of the compounds displayed pronounced biological activity. All these compounds have been characterized on the basis of their UV, IR and NMR spectral results.